Surpassing 13% Efficiency for Polythiophene Organic Solar Cells Processed from Nonhalogenated Solvent - Xiao, Jingyang; Jia, Xiao'e; Duan, Chunhui; Huang, Fei; Yip, Hin‐Lap; Cao, Yong (Advanced materials (Weinheim), 2021)
Benefiting from low cost and simple synthesis, polythiophene (PT) derivatives are one of the most popular donor materials for organic solar cells (OSCs). However, polythiophene‐based OSCs still suffer from inferior power conversion efficiency (PCE) than those based on donor–acceptor (D–A)‐type conjugated polymers. Herein, a fluorinated polythiophene derivative, namely P4T2F‐HD, is introduced to modulate the miscibility and morphology of the bulk heterojunction (BHJ)‐active layer, leading to a significant improvement of the OSC performance. The Flory–Huggins interaction parameters calculated from the surface energy and differential scanning calorimetry results suggest that P4T2F‐HD shows moderate miscibility with the popular nonfullerene acceptor Y6‐BO (2,2′‐((2Z,2′Z)‐((12,13‐bis(2‐butyloctyl)‐3,9‐diundecyl‐12,13‐dihydro‐[1,2,5]thiadiazolo[3,4‐e]thieno[2′,3′:4′,5′]thieno[2′,3′:4,5]pyrrolo[3,2‐g]thieno[2′,3′:4,5]thieno[3,2‐b]indole‐2,10‐diyl)bis(methanylylidene))bis(5,6‐difluoro‐3‐oxo‐2,3‐dihydro‐1H‐indene‐2,1‐diylidene))dimalononitrile), while poly(3‐hexylthiophene) (P3HT) is very miscible with Y6‐BO. As a result, the P4T2F‐HD case forms desired nanoscale phase separation in the BHJ film while the P3HT case forms a completely mixed BHJ film, as revealed by transmission electron microscopy (TEM) and grazing‐incidence wide‐angle X‐ray scattering (GIWAXS). By optimizing the cathode interface and the morphology of the P4T2F‐HD:Y6‐BO films processed from nonhalogenated solvents, a new record PCE of 13.65% for polythiophene‐based OSCs is demonstrated. This work highlights the importance of controlling D/A interactions for achieving desired morphology and also demonstrates a promising OSC system for potential cost‐effective organic photovoltaics. An efficient polythiophene‐based organic solar cell (OSC) is demonstrated based on a fluorinated polythiophene donor with deep highest occupied molecular orbital (HOMO) level and appropriate miscibility with the acceptor. With further interfacial modification by a fullerene self‐assembled monolayer, a record power conversion efficiency (PCE) of 13.65% for polythiophene‐based OSCs is achieved with the device processed from nonhalogenated solvent.